UPAYA MENJADIKAN PERGURUAN TINGGI SWASTA (PTS) SUATU CENTER OF EXSELENCE ANTARA HARAPAN DAN KENYATAAN - Subiyanto, Subiyanto (Universitas Muhammadiyah Magelang, 2009)
This paper aims to determine the level of development, the ideal of progress of private universities in accordance with the demands, desires of the community. The essence of national education policy is the tendency of educational development is directed to the needs, demands of modern society, education Reflections on Private Higher output (graduates) can compensate for lack of absorption stikholder (user's employment), so there is understanding of the quality of graduates of private universities were considered less good. The development of private higher education between expectations and reality there are several things to note are: a) the unity of teaching, research and community service; b) disciplinary approach; c) Cooperation is not imposed; d) The silence and e) Freedom. New educational paradigms in private universities improve the quality of academic, administrative, student affairs led to a satisfactory outcome (a professional labor-oriented needs of the community). The role of private universities is very large, because public universities in the conduct of Tri Dharma universities, public expectations of private universities is very high (large enough), because private universities aspire to the intellectual life of the nation. The elements that support the accountability, quality, relevance, institutional autonomy and cooperation network.